Comparative analysis of the leaf architectural characters of Saurauia bontocensis Merr. and Saurauia polysperma (Blanco) Merr. with the application of Digital Image Analysis Software (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Daipan BPO, Buot IE Jr., Daipan HMO. 2022. Comparative analysis of the leaf architectural characters of Saurauia bontocensis Merr. and Saurauia polysperma (Blanco) Merr. with the application of Digital Image Analysis Software. Biodiversitas 23: 3869-3875. Major confusion still exists among several authors concerning the taxonomy of the dagwey plant. This species is economically significant to the Ikalahan tribe of Luzon, Philippines. Several papers claimed that the plant is Saurauia bontocensis, while others stated that it is Saurauia subglabra. Many botanical websites claimed that S. subglabra is synonymous with S. polysperma, while another article distinguished S. subglabra from S. polysperma. Thus, to help resolve the taxonomic ambiguities, this paper performed a comparative analysis of the leaf architectural characters of S. bontocensis and S. polysperma with the aid of digital image analysis software and cluster analysis. Results revealed that the blade characters alone, delineate the two species, particularly, in terms of the laminar size, shape, symmetry, leaf L:W ratio, base and apex angle, and base shape. Additionally, the leaf venation characters delineate the two species, specifically, on the 2º to 5º vein categories, 2º vein angle, 3º vein course, 3º vein angle to 1º, areolation, freely ending ultimate veins, marginal ultimate venation, and leaf rank. Generally, S. bontocensis have larger, longer, and wider leaves compared with the S. polysperma. The leaf architecture analysis performed in this paper produced a very promising result in differentiating the two Saurauia species and could be used to address some of the taxonomic confusion of these species. The study indicated that S. bontocensis and S. polysperma are two distinct species. Moreover, the use of digital image analysis software was very helpful in the computations of the various blade characters, particularly the digital herbarium exsiccate in the absence of actual leaf samples.